SYNERGIZING TECHNOLOGY-ENABLED SERVICE INNOVATION AND SOCIAL MEDIA MARKETING TO BOOST CUSTOMER LOYALTY AND REVENUE GROWTH IN INDUSTRY 4.0 - Ramdani, Agus; Barasa, Larsen; Winarno, Winarno; Gunawan, April; Nurhayati, Sri (Universitas Riau Kepulauan, 2025)
In the digital era of Industry 4.0, technology-enabled service innovation and social media marketing have become essential strategies for businesses seeking to enhance customer loyalty and drive revenue growth. This study aims to systematically review existing literature to understand how these digital strategies individually and synergistically influence customer retention and financial performance. Using a comprehensive literature review method, peer-reviewed journal articles and conference proceedings published between 2000 and 2025 from the Scopus database were analyzed. The analysis focused on key themes, trends, and research gaps related to the adoption of digital service innovations and social media marketing approaches. The findings reveal that technological innovations such as artificial intelligence-powered chatbots, mobile applications, and digital payment systems significantly improve customer experience through increased convenience, personalization, and service efficiency, thereby fostering loyalty across various sectors. Simultaneously, social media marketing enhances customer engagement via interactive and personalized content, influencer collaborations, and user-generated media, strengthening emotional connections and brand loyalty. The integration of technology-enabled service innovation with social media marketing generates synergistic effects, leading to sustained repurchase behavior and enhanced revenue generation. Challenges remain in effectively measuring financial impacts, developing organizational capabilities, and addressing ethical considerations related to data privacy and digital trust. Overall, this review highlights the critical role of integrated, customer-centric digital strategies in sustaining competitive advantage and financial success in the evolving digital marketplace. Future research should focus on emerging technologies and contextual factors influencing digital innovation effectiveness. This study provides valuable insights for practitioners and researchers aiming to harness digital transformation for customer loyalty and business growth.